Group I mGluR-Mediated Activation of Martinotti Cells Inhibits Local Cortical Circuitry in Human Cortex - Kroon, Tim; Dawitz, Julia; Kramvis, Ioannis; Anink, Jasper; Obermayer, Joshua; Verhoog, Matthijs B.; Wilbers, René; Goriounova, Natalia A.; Idema, Sander; Baayen, Johannes C.; Aronica, Eleonora; Mansvelder, Huibert D.; et al. (Frontiers in Cellular Neuroscience, 2019)
Group I metabotropic glutamate receptors (mGluRs) mediate a range of signaling and plasticity processes in the brain and are of growing importance as potential therapeutic targets in clinical trials for neuropsychiatric and neurodevelopmental disorders. Fundamental knowledge regarding the functional effects of mGluRs upon pyramidal neurons and interneurons is derived largely from rodent brain, and their effects upon human neurons are predominantly untested. We therefore addressed how group I mGluRs affect microcircuits in human neocortex. We show that activation of group I mGluRs elicits action potential firing in Martinotti cells, which leads to increased synaptic inhibition onto neighboring neurons. Other interneuron types, including fast-spiking interneurons, are depolarized but do not fire action potentials in response to group I mGluR activation. Furthermore, we confirm the existence of group I mGluR-mediated LTD of excitatory synapses in human pyramidal neurons. We propose that the strong increase in inhibition and depression of excitatory synapses upon group I mGluR activation likely results in a shift in the balance between excitation and inhibition in the human cortical network.